2017
DOI: 10.1080/10130950.2017.1379759
|View full text |Cite
|
Sign up to set email alerts
|

Interrogating the resilience of women affected by violence

Abstract: Violence against women is a serious health and social problem for women not just in South Africa but across the globe. Violence renders women vulnerable and in most cases seeks to disempower them. However, most women, once out of the violent situation are able to overcome their adversity. Using Ungar's Social Ecology of Resilience Theory as a framework, this paper demonstrates the journey of women affected by violence to overcome their adversity. It does this through interviews with four women temporarily hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…They mentioned what they had already accomplished so far and what was still out there for them to achieve. They, thus, exhibited resilience through their inherent motivations, which is consistent with literature suggesting that personal qualities are motivators helping individuals survive difficult situations ( 67 , 68 ). Once again, this implies women's agency and strength in being able to motivate themselves even without external help to survive the pain they are going through.…”
Section: Discussionsupporting
confidence: 86%
“…They mentioned what they had already accomplished so far and what was still out there for them to achieve. They, thus, exhibited resilience through their inherent motivations, which is consistent with literature suggesting that personal qualities are motivators helping individuals survive difficult situations ( 67 , 68 ). Once again, this implies women's agency and strength in being able to motivate themselves even without external help to survive the pain they are going through.…”
Section: Discussionsupporting
confidence: 86%
“… Gopal and Nunlall (2017 , p. 63) note that “Although much research has been reported on the nature and trends of violence against women, few studies have focussed on what may be regarded as necessary for their ‘survival’ during and post-violence.” Particularly in the context of extant scholarship on conflict-related sexual violence, what also stands out is a lack of attention to the various ways that those who have experienced such violence “survive” in the sense of rebuilding and moving forward with their lives—in interaction with their social ecologies. When scholars writing about conflict-related sexual violence have referred to resilience (see, e.g., Zraly et al, 2013 ; Koos, 2018 ), they have tended to do so in a very abstract and peripheral way that does not substantively engage with the concept, its meaning or its complexity.…”
Section: Resilience In the Context Of Conflict-related Sexual Violencementioning
confidence: 99%
“…Resilience in the Context of Conflict-Related Sexual Violence Gopal and Nunlall (2017) note that 'Although much research has been reported on the nature and trends of violence against women, few studies have focussed on what may be regarded as necessary for their "survival" during and post-violence' (p. 63). Particularly in the context of extant scholarship on conflict-related sexual violence, what also stands out is a lack of attention to the various ways that those who have experienced such violence 'survive' in the sense of rebuilding and moving forward with their lives -in interaction with their social ecologies.…”
Section: Introductionmentioning
confidence: 99%
“…[92]. This may lead to increased vulnerability of the individual [93], shackling resilience and health. Figure 2 depicts the multiple facets of sexual health and their association with psychological resilience.…”
Section: Sexual Health and Emotional Resiliencementioning
confidence: 99%